Income shifting by multinational enterprises as a source of mismeasurement in aggregate statistics - Serena Fatica; Wildmer Daniel Gregori (National Accounting Review)
This paper studies income shifting by European multinational enterprises as a potential source of mismeasurement in aggregate statistics, with a focus on labour productivity. We use firm level data to implement different types of formulary apportionments and to reattribute earnings among entities of multinational groups operating across the European Union (EU). The results suggest that income shifting affects the measurement of the output-per-worker in the corporate sector. Bottom-up approaches grounded in representative microdata can improve its computation.